Second law analysis of fully developed laminar flow for rectangular ducts with semicircular ends - Öztop, Hakan Fehmi; Dagtekin, Ihsan; Sahin, Ahmet Z. (Pergamon-Elsevier Science Ltd, 2009)
Second law analysis is performed analytically for rectangular ducts with semicircular ends in laminar flow. Two different situations are considered for the analysis. In the first case, boundaries of duct are considered in constant wall temperature. In the second case, constant wall heat flux boundary conditions applied. Entropy generation is obtained for various cross sectional areas, various wall heat flux and Reynolds numbers. It is found that with the increasing aspect ratio (beta) values for both constant wall temperature (CWT) and constant heat flux (CHF) total entropy generation increases, however, required pumping power also increases. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Constant heat flux; Entropy; Laminar flow; Duct